Psychometric validation and cultural adaptation of executive functioning scale in Malaysian University students - Hao Yin; Muhammad Syawal Amran (PLoS ONE, 2026)
Addressing the lack of culturally-appropriate assessment tools, this study adapted and validated the Executive Functioning Scale (EFS) for use within a Malaysian university student population. Utilizing a sample of 629 university students, we conducted a comprehensive psychometric evaluation of the adapted scale. Exploratory factor analysis (EFA) supported a refined 50-item, six-factor structure that accounted for 65.87% of the total variance. Subsequent confirmatory factor analysis (CFA) revealed that a second-order hierarchical model—in which the six first-order factors loaded onto a single, higher-order Executive Functioning construct—provided an excellent fit to the data (CMIN/df = 1.447, CFI = .976, RMSEA = .026). Critically, its fit was virtually indistinguishable from a more complex first-order model, strongly favoring the hierarchical conceptualization on the basis of parsimony. The scale also demonstrated strong discriminative validity, effectively differentiating between high- and low-performing groups across all dimensions. Collectively, the findings establish the Malaysian-adapted EFS as a robust and valid instrument for assessing the multifaceted nature of executive functioning. This research provides the first psychometrically sound tool for measuring executive functioning tailored to this population, offering a critical resource for future cross-cultural research, clinical diagnostics, and educational interventions. The validated scale facilitates a more nuanced understanding of cognitive constructs within a non-Western higher education context.